Caracterización de las derivadas precordiales en electrocardiografía para caninos sanos - Vera Basto, Nelson; Arcila , Victor (Spei Domus, 2005)
In human, the lead precordial, have defined importance, however, didn’t know in veterinary medicine of small animals (canine). This work, looked by means of registrations electrocardiography, considering those lead bipolar (I, II, III), unipolares (aVR, aVL, aVF) and precordiales (V2, V4, V5 and V6), in 100 canines, crossbreeds and Poodle, with the objective of characterizing the behavior of the lead precordiales clinically in canine healthy. Choose 50 animals of each race, males and females in same proportion, in a range of 1.5 and 7 years of age. Once the 100 registrations electrocardiographys were obtained, they were interpreted according to the groups, making a descriptive analysis of the tendency of the waves in each lead precordial, based on the measures of central tendency (the medium one, fashion, average, values minimum and maximum, and standard deviation). The values get include the variables outlined for the investigation, what meant that the race, the sex, the age and the weight, they don’t influence significantly in the tendency of the lead precordiales.